Error Analysis in Argumentative Essays Written by the Fifth Semester Students - Lussy Albayinnah; Diemroh Ihsan; Margaretha Dinar Sitinjak (Jurnal Bahasa dan Sastra, 2020)
Abstract: The objectives of this study were to find out: (1) The argumentative essay achievement of the fifth semester students of English Education Study Program of Sriwijaya Uuniversity, (2) kinds of errors in argumentative essays made by the same students, (3) possible causes of errors in argumentative essays made by them, (4) kinds of errors mostly found in argumentative essays made by the students, and (5) possible ways to eliminate errors made by them..The sample of this study were 20 fifth semester students selected by employing stratified sampling from two different class campuses--Indralaya and Palembang.  Argumentative essay writing tests were used to collect the data which were then analyzed by using two error taxonomies, namely Surface Strategy Taxonomy and Linguistic Strategy Taxonomy. The result showed that the students’ argumentative achievements reached the Meeting Standard score with 8.5 as the highest score and 6 as the lowest score. Errors in Grammar, Lexicon, Semantics, Syntax, and Mechanics as well as in Omission, Addition, Misformation, and Misorder were found, which were caused by one or two of the following factors: overgeneralization, first language interference, and/or carelessness. Among those errors,  errors on grammar and omission were mostly found. Some suggested ways to eliminate errors include doing remedial teaching focussing on teaching material covering the use of punctuation, conjunction, subordinate conjunction, and a brief theory about translation. Keywords: argumentative essay, error analysis, linguistic category taxonomy, surface strategy taxonomy Abstrak: Tujuan penelitian ini adalah untuk mengetahui (1) pencapaian kemampuan mahasiswa semester 5 Program Studi Pendidikan Bahasa Inggris Universitas Sriwijaya dalam menulis esei argumenatative, (2) jenis kesalahan yang dibuat oleh mereka, (3) kemungkinan penyebab terjadinya kesalahan tersebut, (4) jenis kesalahan yang paling banyak terjadi, dan (5) beberapa cara yang mungkin dapat diterapkan untuk mengurangi terjadinya kesalahan-kesalhan tersebut. Sampel penelitian ini terdiri dari 20 orang mahasiswa pada program studi yang sama yang dipilih dengan menggunakan teknik pengambilan sampel secara bertingkat dari dua lokasi kampus—Inderalaya  dan  Palembang.  Tes  dalam  menulis  esei  argumentattive  digunakan untuk mengumpulkan data yang diperlukan yang kemudian di analisis menggunakan dua cara untuk mengetahui jenis kesalahan (two error taxonomies), yakni Surface Strategy Taxonomy dan  Linguistic  Strategy Taxonomy.  Hasil  penelitian  ini  menunjukkan  bahwa  kemampuan mahasiswa dalam menulis esei argumentative mencapai nilai standar cukup bagus, 8.5 untuk nilai tertinggi dan 6 untuk nilai terendah. Jenis kesalahan yang ditemukan berkaitan dengan tatabahasa, kosakata, makna, sintaks, mekanik, penghapusan, penambahan, salahpembentukan, dan salah susun. Kesalahan-keasalahan tersebut disebbkan oleh salah satu atau dua dari faktor overgeneralization, first language interference, and/or carelessness.Di antara beberapa jenis kesalahan di atas, keasalahan yang paling banyak ditemukan adalah kesalahan dalam tatabahasa dan penghapusan (omission). Beberapa cara yang mungkin dapat diterapkan oleh dosen untuk mengurangi atau membatasi terjadinya kesalahan oleh para mahasiswa adalah  mengadakan perbaikan proses pengajaran,  misalnya yang mencakup  materi ajar seperti cara penggunaan tatabaca, kata penghubung, termasuk teori singkat tentang penerjemahan. Kata-kata kunci: argumentative essay, error analysis, linguistic category taxonomy, surface strategy taxonomy